(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
The article analyzes human participation in the economic system in terms of its functional role and institutional position in the reproductive process, including female human capital. The proposed phase-by-phase classification of participation provides a detailed analysis of the formation, accumulation and realization of human capital, allows us to identify the features of the involvement of various social groups and assess the impact of each phase on economic development, social well-being and the development of effective institutional and managerial measures for the reproduction of human capital.